Festuca macutrensis Zapal. (Poaceae) у флорі Центрального Полісся. I. Особливості анатомо-морфологічної диференціації - Беднарська, І.О.; Орлов, О.О. (Український ботанічний журнал, 2011)
Во флоре Центрального Полесья найден новый для региона вид — Festuca macutrensis Zapał. На основании анализа 12 морфологических показателей и 16 признаков анатомического строения листовых пластинок исследовано дифференциацию 8 популяций этого вида с окрестностей Житомира. Последние сравниваются с подольскими популяциями основной части ареала вида, в том числе с locus classicus. Изучена изменчивость диагностических показателей вида в природных и нарушенных экотопах. Выяснено, что житомирские популяции имеют комплекс экологических и морфологических отличий и могут рассматриваться как особая эколого-географическая расса вида. Festuca macutrensis Zapał was found for the first time in the flora of the Central Polissya area. Based on analysis of 12 morphological and 16 anatomical characters of leaf blade, differentiation within 8 populations of this species from Zhytomyr environs was studied. They were compared with those in populations from Podillya, the main part of the species range including locus classicus. Variability of the diagnostic species characters was studied in the natural and disturbed environment. It was determined that Zhytomyr populations have different ecological and morphological features and they can be considered as a peculiar ecological and geographical race of the species.